Socio-Demographic Factors Affecting the Treatment Outcome in Patients of Tuberculosis - Sadana, Pooja; Singh, Tejbir; Deepti, S S (National Journal of Community Medicine, 2015)
Introduction: Tuberculosis is today the biggest infectious killer among young people and adults. Besides the disease burden, tuber- culosis also causes an enormous socio-economic burden to India. DOTS have certainly put a dent to the problem of tuberculosis but still the desired results are not achieved. The present study is an at- tempt to know about the socio-demographic factors affecting the treatment outcome in patients of tuberculosis under DOTS. Methods: The study was conducted on a total of 326 patients who were residing in the area of PHC Verka and registered with District Tuberculosis Centre, Amritsar. House to house visits were done and information about the socio- demographic parameters were recorded on a pretested and preformed questionnaire evolved for the study. Results: Majority, 43.40% patients belong to 15-29 yrs of age. 57.90% were males and 42.10% were females. Male to female ratio was 1.37:1. Present study reveals that 90.6% of females had favourable outcome while favourable outcome was seen in 80.3% males. The result was found to be statistically significant (p=0.03). Relation between the literary status and outcome was found to be significant (p=0.03). Conclusion: Socio -demographic factors affecting the treatment out- come were sex and literary status. Marital status, socioeconomic sta- tus, type of house, type of family and overcrowding were not signifi- cantly associated with treatment outcome.